Variabel Pengajuan Sertifikasi Halal Usaha Kecil Keripik Tempe di Kota Malang - Sucipto Sucipto; Elvira Moudhy Syahputri; Riska Septifani (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Malang is one of the halal tourism destinations in Indonesia. Halal certification of superior food souvenirs such as tempeh chips is important to support halal tourism. In fact, the small business of halal certified chips is still limited. This study aimed to identify variables that affect the tempeh crispy small business submission for halal certification. The study used the Partial Least Square (PLS) method. Data was obtained from a questionnaire of 40 respondents consisting of 20 tempeh chips not halal certified and 20 businesses that were halal certified. Research variables include producer awareness, halal certification procedures, halal certification costs, halal certification regulations, and consumer demand. The results showed that the variable halal certification regulations and consumer demand significantly influence the submission of halal certification. Awareness and knowledge of producers of the procedures, costs, and benefits of halal certification can be increased in collaboration with the Halal Product Guarantee Agency (HPGA), the industrial offices of local government, and universities to provide information, improve, and assist producers to submit halal certification.